DNA Methylation Affects the Efficiency of Transcription Activator-Like Effector Nucleases-Mediated Genome Editing in Rice - Kaya, Hidetaka; Numa, Hisataka; Nishizawa-Yokoi, Ayako; Toki, Seiichi; Habu, Yoshiki (Frontiers in Plant Science, 2017)
Genome editing in plants becomes popular since the advent of sequence-specific nucleases (SSNs) that are simple to set up and efficient in various plant species. Although transcription activator-like effector nucleases (TALENs) are one of the most prevalent SSNs and have a potential to provide higher target specificity by their dimeric property, TALENs are sensitive to methylated cytosines that are present not only in transposons but also in active genes in plants. In mammalian cells, the methylation sensitivity of TALENs could be overcome by using a base-recognition module (N*) that has a higher affinity to methylated cytosine. In contrast to mammals, plants carry DNA methylation at all cytosine contexts (CG, CHG, and CHH, where H represents A, C, or T) with various degrees and effectiveness of N* module in genome editing in plants has not been explored. In this study, we designed sets of TALENs with or without N* modules and examined their efficiency in genome editing of methylated regions in rice. Although improvement in genome editing efficiency was observed with N*-TALENs designed to a stably methylated target, another target carrying cytosines with various levels of methylation showed resistance to both normal and N*-TALENs. The results suggest that variability of cytosine methylation in target regions is an additional factor affecting the genome editing efficiency of TALENs.